Manifestation of Immunocorrective Effect of Cryopreserved Feta Liver Cells Under Development of Graft-Versus-Host Disease - Yampolskaya, Ekaterina E.; Matsevitaya, Irina Yu.; Gaevskaya, Yuliya A.; Lutsenko, Elena D.; Ostankov, Maksim V.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â  Probl Cryobiol Cryomed 2014; 24(2):168.